MUTYH Gene Polymorphisms as Risk Factors for Rheumatoid Arthritis - Wan, Lei; Huang, Yong-San; Hsu, Yu-An; Chen, Ter-Hsin; Lin, Hui-Ju; Huang, Chung-Ming; Tsai, Kun Shi; Kung, Yung-Jen; Chang, Ching-Yao (BioMed research international, 2015)
Objectives. MUTYH glycosylase involved in DNA repair pathways may be associated with the risk of autoimmune diseases such as rheumatoid arthritis (RA). Therefore, the association between polymorphisms in the MUTYH gene and RA was evaluated. Methods. We recruited 192 RA patients and 192 healthy subjects in Taiwan. The 4 MUTYH polymorphisms (rs3219463, rs3219476, rs3219489, and rs3219493) were detected and haplotype analysis was performed using the Bayesian method. The genotype and allelic frequency distributions of the polymorphisms in both RA patients and healthy patients were compared by the chi-square test. Results. Comparison of the genotype/allele frequencies between individuals with RA and the control groups revealed significant differences in 2 MUTYH gene polymorphisms, rs3219463 and rs3219476. After we performed a haplotype-specific analysis, the haplotypes Ht6-GTGC and Ht8-GGCG had lower presenting rates in RA patients than in the control groups. Furthermore, the genotype frequency of rs3219463 G/ was significantly increased among patients with immunoglobulin M rheumatoid factors, whereas that of rs3219476 was not. Conclusion. We demonstrated that the rs3219463 and rs3219476 polymorphisms in RA patients from a Taiwan Chinese population were associated with disease susceptibility. These data indicate that the MUTYH gene may play a role in the progression of RA.